CURRANTS (RIBES L., GROSSULARIACEAE) IN THE PETER THE GREAT BOTANICAL GARDEN - G. A. Firsov; L. F. Yandovka (Труды по прикладной ботанике, генетике и селекции, 2018)
The Peter the Great Botanical Garden of the V. L. Komarov Botanical Institute (BIN), Russian Academy of Sciences, is one of the leading  centers of arboriculture in the North-Western Russia. A majority of  representatives of the genus Ribes L. are winter-hardy and very  ornamental. There are 16 species and 2 forms in the Garden's  modern collection. All taxa, except R. biebersteinii Berl. ex DC.,  produce flowers and fruits. There are certain samples of considerable age, up to 100 years old. In recent years, in the early  21st century, the collection has continued to be replenished with new species and samples. There are a number of species and forms  promising for urban landscaping in St. Petersburg and other cities of  the North-Western Russia, and for wider distribution outside botanic  gardens: Ribes diacantha Pall., R. sachalinense (Fr. Schmidt) Nakai,  R. sanguineum Pursh, etc. Many species are valuable berry- producing shrubs, honey-yielding, medicinal and ornamental plants.  They are suitable for urban landscape architecture, city parks, or  afforestation. Besides, they are of special interest for planting in  stony plots and rocky gardens. There are considerable reserves to  replenish the collection of the Peter the Great Botanical Garden both  in the contexts of repeated (R. fasciculatum Siebold et Zucc.) or  primary introduction of Ribes taxa (R. menziesii Pursh, R. ambiguum Maxim. etc.). There are new species in the arboreal nursery of the  Botanic Garden, such as R. atropurpureum C.A. Mey., which may  occupy their permanent place in the Garden in the coming years.  The present article is based on the data of the 2017 inventory, and  has been prepared within the framework of the forthcoming  publication Annotated Catalogue of the Outdoor Collection of Living  Plants at the Peter the Great Botanical Garden.